NOTE ON THE NATURAL PEARL OF PLACENTA PLACENTA (LINNAEUS) - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
There is an extensive bed of Placenta placenta in the Kakinada Bay. About26.2% of the population contains natural pearls which are fornaed on buccalmass, gonad and mantle. The frequency of occurrence of pearls in larger individualsis greater than that in smaller individuals. The pearls are lustrous andin most cases are spherical. Most of the pearls are smaller than 3 mm.